PENGARUH AMALIYAH IBADAH SHALAT JAMAAH TERHADAP KEDISIPLINAN SANTRI DI PONDOK PESANTREN PUTRI WALISONGO CUKIR JOMBANG - Hajarul Husna, Dewi; Anshori, Sholihul (EL-Islam, 2023)
to carry out the practices that have been regulated by Islamic law. One form of worship that must be fulfilled is congregational prayer. Congregational prayer is a form of teaching for a Muslim to have a disciplined attitude. With discipline, life will be more organized and it will be easy to achieve success in life. The following are research objectives 1) To discover the amaliyah of congregational prayer at PPP. Walisongo Cukir Jombang. 2) To discover the discipline in PPP. Walisongo Cukir Jombang. 3) To discover the influence of amaliyah worshiping congregational prayers on the discipline of students in PPP. Walisongo Cukir Jombang. This study employs a quantitative method.. The population at the PPP. Walisongo Cukir Jombang is 1.400 students, so a sample of 140 students was taken. Data collection in this study pass the use of a questionnaire distribution. Descriptive analysis is the method of data analysis used, prerequisite testing stage and simple analysis of linear regression with the help of SPSS 17. The study's findings lead to the following conclusion 1) The practice of congregational prayer at PPP. Walisongo Cukir Jombang is in the good category, because the score obtained lies between a score of 56-64. 2) Discipline of students at PPP. Walisongo Cukir Jombang is in the pretty good category, because the scores obtained lie between scores of 29-37. 3) There is a substantial connection between the amaliyah of congregational prayer services on the discipline of students at PPP. Walisongo Cukir Jombang. The extent of the influence of amaliyah worship in congregational prayers on the discipline of students is 18.6% and the remaining 81.4% is influenced by other non-examined aspect.